Ադանայի 1909թ. կոտորածը Օսմանյան խորհրդարանի քննարկումներում. հայ երեսփոխանների դիրքորոշումը - Բաբայան, Նաիրա («Զանգակ - 97»)
The present articlc cries to draw a light on the events of 1909 Adana massacrc, in particular it aims to display the position of Armenian depulics in achieving punishment for the criminals, subjecting them to responsibility, providing financial compensaiion to the suffered people, and, above all, in getting rid of the Turkish blames addressed to them. Under the pressure of active discussions and demands of the Armenian dcputics the Ottoman Parliament underlook certain sleps toward balancing the creatcd lense Situation; and yet, these casual attempts to punish the criminals cou!d bc in no comparison with the scope of the crime itself.
Keywords: Հայոց պատմություն; Քաղաքականություն